Soil respiration in shrub willow (Salix x dasyclados) biomass crop increased on the third year after removal - Aydin, Miraç (Inderscience Publishers, 2018)
The SWBC production system is not only a source of renewable energy, but also a carbon sink. However, one of the uncertainties in the greenhouse gas potential analysis of this system is soil CO2 efflux (Fc) rates after its termination. We examined the Fc rates for three years and determined the total CO2 production of SWBC fields following the termination and removal of SWBC fields. Four current SWBC fields of 5-, 12-, 14-, and 19-years old were used as sampling plots. The mean Fc rates did not differ statistically between ages (p = 0.66), and there was no significant interaction effect between age and year (p = 0.94). However, Fc rates significantly increased in the third year (p = 0.01). Annual cumulative Fc ratios at different seasons were 52% for summer, 26% for fall, 16% for spring, and 6% for winter.
Keywords: 13. Climate action; 15. Life on land